2003
DOI: 10.1002/cite.200390048
|View full text |Cite
|
Sign up to set email alerts
|

Bestimmung von Ionenaktivitätskoeffizienten in wässrigen Lösungen mit Hilfe ionenselektiver Elektroden

Abstract: Für die Modellierung der Versuche mit reaktiven Mischungen wurde aufgrund dieser Ergebnisse die Modellvariante offene Verdampfung gewählt.Abb. 8 zeigt ein typisches Ergebnis einer Modellvorhersage, die mit dem oben beschriebenen Stufenmodell für die partielle reaktive Verdampfung einer Formaldehyd/ Wasser-Mischung erzielt wurde. Die Übereinstimmung zwischen den Messwerten und den Modellvorhersagen ist nicht nur für die pauschalen Zusammensetzungen des Kopf-und Sumpfprodukts gut, sondern auch für die besonders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 8 publications
2
30
0
Order By: Relevance
“…In addition, Lin and Lee [12], Lee et al [13], and Schneider et al [14,15] have performed similar measurements and confirmed our results. The theory supporting the method used for these measurements was further elaborated in the work by Rodil and Vera [10] and all values of individual ions activity coefficients measured by our group were recently revised to correct for an error in sign of the term used to estimate the junction potential [11].…”
Section: Introductionsupporting
confidence: 95%
See 2 more Smart Citations
“…In addition, Lin and Lee [12], Lee et al [13], and Schneider et al [14,15] have performed similar measurements and confirmed our results. The theory supporting the method used for these measurements was further elaborated in the work by Rodil and Vera [10] and all values of individual ions activity coefficients measured by our group were recently revised to correct for an error in sign of the term used to estimate the junction potential [11].…”
Section: Introductionsupporting
confidence: 95%
“…In any case, these numbers are not constant in the range of integration required by Eq. (14). Only assuming, as Malatesta does [25], that S − is exactly identical to (−RT/F) and t + is constant, we would obtain:…”
Section: Discussion Of Malatesta's Queriesmentioning
confidence: 98%
See 1 more Smart Citation
“…The basic question is: 'Are the ionic activity coefficients measurable as claimed by us (Khoshkbarchi and Vera, 1996;Wilczek-Vera et al, 2004, 2010Wilczek-Vera and Vera, 2009a) and also by other researchers (Shatkay and Lerman, 1969;Lee et al, 2002;Schneider et al, 2003Schneider et al, , 2004Zhuo et al, 2008) or, as claimed by Malatesta (2009Malatesta ( , 2010 the real values are still unknown?' The term 'real' is used here in the sense of the actual value of the physical property, the value that can be used for chemical engineering design.…”
Section: General Considerations On the Measurability Of Activitiesmentioning
confidence: 96%
“…We will not repeat the arguments here, but the interested reader can find in recent literature (Malatesta, 2006a;Wilczek-Vera et al, 2006a) all details and pertinent references of previous discussions on the subject. Although independent measurements in other laboratories (Lee et al, 2002;Schneider et al, 2003Schneider et al, , 2004 have confirmed the repeatability of results obtained by the method proposed by Khoshkbarchi and Vera (1996) to measure individual ionic activities, it may be argued that the same biased assumptions were used in all cases. This work presents innovative experiments designed to provide independent tests of the method to measure the activity of individual ions.…”
Section: Introductionmentioning
confidence: 77%